Psikologi Agama dan Studi Islam - Siti Juraida Hasibuan; Melinda Saputri Pulungan; Anas Habibi Ritonga (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Psychology of religion is a branch of psychology that examines the relationship between human psychological aspects and religious experiences and behaviors. In the context of Islamic studies, psychological approaches play an important role in understanding spirituality, inner dimensions, and the religious behavior of Muslims in everyday life. This paper aims to examine the definition and scope of psychology of religion, its major approaches, prominent scholars and their influential works, applications of psychology in Islamic studies, and the significance of psychological approaches in the study of Islam. This study employs a library research method with a descriptive-analytical approach by reviewing various relevant literature sources. The findings indicate that psychology of religion contributes significantly to understanding religious development, mental health, spiritual experiences, and the formation of Islamic identity. Furthermore, psychological approaches support the development of Islamic psychotherapy, Islamic education, and efforts to promote social harmony within society. Therefore, the integration of psychology and Islamic studies is an important approach in addressing various religious and psychological issues in the modern era. Keywords: Psychology of Religion, Islamic Studies, Spirituality, Mental Health, Islamic Psychology.   Abstrak       Psikologi agama merupakan cabang ilmu yang mengkaji hubungan antara aspek psikologis manusia dengan pengalaman dan perilaku keberagamaannya. Dalam konteks studi Islam, pendekatan psikologi berperan penting dalam memahami dimensi batin, spiritualitas, serta perilaku umat Islam dalam kehidupan sehari-hari. Makalah ini bertujuan untuk mengkaji definisi dan ruang lingkup psikologi agama, pendekatan-pendekatan utama yang digunakan dalam psikologi agama, tokoh-tokoh beserta karya-karya pentingnya, contoh penerapan psikologi dalam kajian Islam, serta signifikansi pendekatan psikologis dalam studi Islam. Penelitian ini menggunakan metode studi kepustakaan (library research) dengan pendekatan deskriptif-analitis melalui pengkajian berbagai sumber literatur yang relevan. Hasil kajian menunjukkan bahwa psikologi agama memberikan kontribusi yang signifikan dalam memahami perkembangan keberagamaan, kesehatan mental, pengalaman spiritual, serta pembentukan identitas keislaman. Pendekatan psikologis juga mendukung pengembangan psikoterapi Islami, pendidikan Islam, dan upaya membangun harmoni sosial dalam masyarakat. Dengan demikian, integrasi psikologi dan studi Islam menjadi salah satu pendekatan yang penting dalam menjawab berbagai persoalan keagamaan dan psikologis di era modern.   Kata kunci: Psikologi Agama, Studi Islam, Spiritualitas, Kesehatan Mental, Psikologi Islam.